Two-Step Cryopreservation of Goat (Capra hircus) Semen Using Fresh Coconut Water as Egg Yolk Substitute in a Tris–Citric Acid–Glycerol-Based Extender - Ofilas, Pauline (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the effectiveness of fresh coconut water (Cocos nucifera L.) as an alternative cryoprotective component in a Tris–citric acid–glycerol extender for goat (Capra hircus) semen using a two-step cryopreservation protocol. A completely randomized design was employed with four treatments, including a conventional egg yolk-based control and three coconut water concentrations (25%, 50%, and 75%), with four replicates per treatment across three collection sessions. Semen collected from three healthy bucks was pooled, processed, cryopreserved, and evaluated after 24 hours using Computer-Assisted Sperm Analysis for progressive and total motility. Results showed no statistically significant differences among treatments; however, the 50% coconut water formulation consistently produced the highest numerical values for both progressive and total motility, slightly exceeding the control. Lower and higher concentrations resulted in reduced motility, indicating a concentration-dependent response. The two-step protocol effectively minimized osmotic stress during cryopreservation. Despite the absence of statistical significance, findings suggest that 50% coconut water has potential as a viable alternative to egg yolk-based extenders. The study recommends increasing sample size, expanding sperm quality assessments, standardizing coconut water preparation, and conducting in vivo fertility trials. This research aligns with SDG 2 (Zero Hunger) and SDG 12 (Responsible Consumption and Production) by supporting improved livestock productivity and promoting sustainable, plant-based alternatives in agricultural biotechnology. The findings contribute to socio-economic and technological sustainability by offering a locally accessible, cost-effective solution for improving reproductive efficiency in goat production systems.